Perancangan dan Analisis Kinerja Protokol MAC IEEE 802.11 Berbasis Antena Cerdas untuk Jaringan Ad Hoc Aplikasi Radar Pelacak - Nurmayanti Zain; Abdul Hakim Udin; Muh Irham M (Jurnal Krisnadana, 2025)
This study proposes the design of an IEEE 802.11-based MAC protocol for ad hoc networks by integrating smart antenna technology, aimed at enhancing communication performance in radar tracking applications. The research uses a quantitative approach with a deductive methodology, employing simulation modeling coded in C language via Microsoft Visual C++ 2010 Express. Two types of antennas were compared: an omnidirectional antenna and a directional smart antenna. Simulations were conducted using two network topologies—string and mesh—under scenarios with and without smart antenna support. Performance was measured based on throughput, collision probability, and success rate. Results show that the smart antenna-based MAC protocol significantly outperforms the conventional setup. In the string topology, the system achieved a maximum throughput of 1.5 Mbps, a collision probability as low as 0.001 or even zero, and a perfect success rate of 1 in both topologies. These findings confirm that the integration of smart antennas into MAC protocols improves data exchange efficiency and network reliability, especially in ad hoc radar tracking environments.